Different Medical Image Registration Techniques: A Comparative Analysis - Karthick, Suyambu; Maniraj, S. (Current Medical Imaging, 2019)
Background: Image registration provides major role in real world applications and classic digital image processing. Image registration is carried out for more than one image and this image was captured from a different location, different sensors, different time and different viewpoints. Discussion: This paper deals with the comparative analysis of various registration techniques and here six registration techniques depending upon intensity, phase correlation, image feature, area, control points and mutual information are compared. Comparative analysis for different methodologies shows the advantages of one method over the other methods. The foremost objective of this paper is to deliver a complete reference source for the scholars interested in registration, irrespective of specific application extents. Conclusion: Finally performance analyses are evaluated for the medical datasets and comparison is graphically shown with the MATLAB simulation tool.
Keywords: feature detection